THE INFLUENCE OF STUDENT PERCEPTION OF ENTREPRENEURSHIP AND FAMILY ENVIRONMENT TOWARD ENTREPRENEURIAL INTENTION (STUDY OF SMK STUDENTS IN PADANG) - Fadli Muzdalifah; Susi Evanita (Universitas Negeri Padang, 2019)
The purposes of this research are to analyze: The effect of student perception of entrepreneurship on entrepreneurial intention of SMK Students in Padang and The effect of family environment on entrepreneurial intention of SMK Students in Padang. The type of this research is causative research. The population for this research is all students of SMK in Padang. The total sample of this research was 200 people by using a questionnaire. The result of this research shows that student perception of entrepreneurship has significant effect on entrepreneurial intention of SMK students in Padang and family environment has no significant effect on entrepreneurial intention of SMK students in Padang. The conclusion from this research is student perception of entrepreneurship show a significant effect on an entrepreneurial intention of SMK Students in Padang and Family environment there is no significant effect on an entrepreneurial intention of SMK Students in Padang. For the future research, it is better to increase the support of parents to their children to entrepreneurship and improve entrepreneurship activities that can influence entrepreneurial intention.Keyword: Student Perception of Entrepreneurship, Family Environment, Entrepreneurial Intention